Clients with different problems are different and questionnaires are not blood tests: A template analysis of psychiatric and psychotherapy clients' experiences of the CORE‐OM. Issue 2 (6th January 2020) - Paz, Clara; Adana‐Díaz, Lila; Evans, Chris
Abstract: Aim: To explore the constructions users of mental health services have of outcome and change measures, contrasting those of hospital psychiatric patients with psychotic experiences versus psychotherapy clients in private practice who have not had psychotic experiences. Method: Twenty‐four participants, 12 from each setting, were interviewed about their experiences when answering the Clinical Outcomes in Routine Evaluation‐Outcome Measure. Template analysis was used to analyse transcripts from a pragmatic and contextualist position. Findings: Participants from both settings understood all the items of the CORE‐OM and generally saw it as useful to assess the psychological distress and to appreciate the progress within the treatment. However, experience of emotions such as sadness and hopelessness, a focus on functioning and an emphasis on impartiality of the person who offers the questionnaire were themes that emerged only for the hospital participants. This is the first study explicitly comparing the experiences of two types of users of mental health care services when answering the CORE‐OM; with the increasing routine use of change measures, reactions of these groups to such measures need to be explored in more detail qualitatively as well as quantitatively. Clinicians in all settings should think carefully about the explanations for the use of change measures, being sure that they address the primary concerns of participants. Scores are not like blood test results, and they arise in the relational context, a construction that includes both local organisational and cultural location.